Eneagrama: definición y fundamentos - Beatriz Cuyás, Elena (Miscelánea Comillas, 2009)
The Enneagram, an ancient theory about personality, reveals a universal knowledge abouth the human being and invites us to work deep in ourselves,with the intention of becoming a fair person, overcoming the mask of the personality.The Focusing Method, centered in the body, comes from the experiencial psicology and opens a way to find the inner-truth, implicit in the body knowledge.In this work we make a theoretical synthesis of both disciplines integrating themin a workshop based on the Focusing Method.